Positioning Pelita's Superria Outlet In Kota Samarahan / Abdul Rahman Deen ... [et al.] - Deen, Abdul Rahman; Hj. Alwi, Rashidee; Chong, Fen Nee; Chong, Vui Hok; Abg Abdul Rahman, Abg Zainoren; Atan, Patrick; Amir Abdullah, Ardiana Mazwa Raudah; Mahdi, Ahmad Faisal; James, Wealy (2008)
As the leading state agency entrusted with the responsibility of taking the lead in spear heading Sarawak's economic development and generating wealth for the state, PELITA has successfully established itself as a premier player in several important economic sectors such as tourism, property development and plantations. As a dynamic catalyst entrusted with the task of spurring on the State's economy PELITA continues to explore and develop new and innovative business opportunities.